The Limits of Ancient Christianity
Once considered a period of decline, Late Antiquity (third through eighth centuries C.E.) is now seen as a creative period of transition between the ancient and medieval worlds. Ostensibly an "otherworldly" religion, Christianity became a powerful worldly cultural force. But this power was shaped and severely limited by a large number of factors, including its own highly diverse traditions, scriptures, practices, and theologies. William Klingshirn and Mark Vessey have assembled some of the most influential scholars in the study of Late Antiquity to test the limits of Christianity. The sixteen essays in this collection investigate the ways in which the concept of "limits" (temporal, spatial, ideological, social, and cultural) can help us to understand the texture of Christianity during this formative period. Taken together, the essays in this volume constitute as yet the most sustained study of cultural transformations evoked by Robert Markus's phrase "the end of ancient Christianity." This timely volume will interest students of early Christian history and theology, as well as historians of the Roman empire and early middle ages. Because it examines a formative period of western civilization, it will also speak to anyone who wonders why Christianity takes the form it does today. Contributors include Gerald Bonner, Peter Brown, Virginia Burrus, John Cavadini, Elizabeth Clark, Paula Fredriksen, Sidney Griffith, David Hunter, Conrad Leyser, Paul Meyvaert, Oliver Nicholson, James O'Donnell, Philip Rousseau, Frederick Russell, Carole Straw, and Robert Wilken. William E. Klingshirn is Associate Professor of Greek and Latin, The Catholic University of America. Mark Vessey is Associate Professor of English, University of British Columbia.